Effect of rams’ social hierarchy upon scrotal circumference, semen quality, and copulation performance under arid land conditions - Gerardo Véliz-Deras, Francisco; González-Tavizón, Andrea; Meza-Herrera, César Alberto; Mellado, Miguel (Emirates Journal of Food and Agriculture, 2023)
Social hierarchies among animal species are based on the animal ́s dominance-aggressiveness level aligned with the subordination of their mates. Social order is mostly defined by animal size, live weight, or age. This study aimed to evaluate the association between odor score (OS), horn presence (HP), horn size (HS), and body temperature on social rank hierarchy, scrotal circumference (SC), semen quality (SQ), and sexual drive (SD). Adult Dorper rams (n=24) with similar live weight (LW), body condition score (BCS), and age (AG) were subjected to a behavioral test to define a success index (SI) based on male-to-male interactions. OS was highest (P<0.05) for rams with high social rank (HSR; 2.5±0.4) and lowest for rams with low social status (LSR; 0.75±0.01). Scrotal circumference was highest (P<0.05) for HSR rams (40.0±3.5) and lowest for rams with medium social rank (MSR; 29.3±1.20). Sperm cell concentration/mL was highest (P<0.05) for HSR rams (3848±187) and lowest for LSR (2660±463). 80% of the HSR rams had horns, while 33.3 of the LSR rams were hornless. The percentage of rejection to mount an estrous ewe was 77.7 for LSR and 20% for HSR and MSR rams (P <0.05). To conclude, the HSR rams presented the highest successful copulation, scrotal circumference, and sperm cell concentration compared to rams with lesser social rank scores